Analysis of Quality of Knowledge Transformation Path to Learning Organization at Copper Carving Cluster in Central Java - Widiartanto, Widiartanto (Information Management and Business Review, 2014)
The purpose of this study was to determine the effect among variables of disciplinary learning organization (personal mastery, mental models, shared vision, thinking systemic, and team learning). The benefit of this research is to develop a model of knowledge transformation path quality as one of the strategies to manage environment change around Copper Craft Cluster. Samples of 90 workers were chosen by Slovin at 10% critical value of 716 populations as workers at the Copper Carving Cluster Tumang Boyolali, Central Java as a chosen research location. The technique sampling was proportional random sampling. The validity and reliability were tested. The data analysis method has been used descriptive analysis and inferential statistics (used path analysis). The benefit of this research was to develop a model of quality of knowledge transformation path as one of the strategies to manage environment’s change at the Copper Craft Cluster. The results showed that there were a positive and significant influences among variables as follow: personal mastery discipline on mental models discipline ; personal mastery discipline on shared vision discipline; personal mastery discipline on systemic thinking discipline; mental models discipline on shared vision discipline; mental models discipline on systemic thinking discipline; systemic thinking discipline on shared vision discipline; mental models discipline on team learning discipline; systemic thinking discipline on team learning discipline; and shared vision discipline on team learning discipline.